2013
DOI: 10.3892/ijo.2013.2121
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of YAP through an Akt-dependent process by 3, 3′-diindolylmethane in human colon cancer cells

Abstract: Cancer development is a complex process governed by the interaction of several signaling pathways. The Hippo and PI3K/Akt pathways have been shown to play a critical role in controlling tissue growth involved in the regulation of cell proliferation. 3, 3'-diindolylmethane (DIM) is a natural compound that selectively kills cancer cells without causing toxicity to normal cells. This study aims to investigate whether DIM has an effect on the Hippo signaling pathway mediated via the PI3K/Akt signaling pathway in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…DIM, a non-toxic dietary chemopreventive agent, has been investigated for preventing, inhibiting and reversing the progression of various types of cancer (32). Many studies have suggested that DIM is strongly associated with tumor growth suppression mediated by several signaling pathways in human carcinomas (9,(17)(18)(19)(20)24,32). We found that DIM significantly inhibited gastric cancer cell growth in a dose-dependent manner and potentiated the antitumor effects of paclitaxel in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…DIM, a non-toxic dietary chemopreventive agent, has been investigated for preventing, inhibiting and reversing the progression of various types of cancer (32). Many studies have suggested that DIM is strongly associated with tumor growth suppression mediated by several signaling pathways in human carcinomas (9,(17)(18)(19)(20)24,32). We found that DIM significantly inhibited gastric cancer cell growth in a dose-dependent manner and potentiated the antitumor effects of paclitaxel in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 68%
“…Turati et al (12) and Guercio et al (16) reported that high allium vegetable consumption reduces gastric cancer risk, and a high intake of cruciferous vegetables was found to be inversely associated with the risk of gastric cancer in humans in a study by Wu et al (15). The compound 3,3'-diindolylmethane (DIM) is a component of cruciferous vegetables that inhibits tumor growth through induction of apoptosis in various types of cancer cells (17)(18)(19)(20). Our previous study demonstrated that DIM suppressed gastric cancer cell growth via activation of the Hippo signaling pathway (17).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous study reported that Hippo signaling and Akt pathway controlling cell proliferation by PI3K inhibitor and DIM treatment in colon cancer cells [15]. In addition, DIM induced G1 cell cycle arrest that coincided with a strong induction of P21 gene expression and promoter activity in both estrogen responsive and nonresponsive breast cancer cells [16].…”
Section: Introductionmentioning
confidence: 99%